Adapting behavioral activation for patients receiving medications for opioid use disorder in primary care: a pilot study - Hooker, Stephanie A.; Kim, Hanmin; Lonergan-Cullum, Mary; Busch, Andrew M.; Nissly, Tanner; Levy, Robert (Frontiers in Psychology, 2024)
Introduction Effective adjunctive therapeutic treatments for patients with opioid use disorder (OUD) on medication for OUD (MOUD) in primary care settings are needed to address high rates of mental illness and stress. Behavioral activation (BA) is a brief, evidence-based therapy that has potential to improve quality of life in people with OUD. The purpose of this pilot study was to evaluate the feasibility and acceptability of values-based BA (VBA) as an adjunct treatment for patients receiving MOUD in primary care. Methods Participants were recruited for a single-arm pilot trial of BA in a primary care setting. VBA was adapted for people with OUD and included 4–6 sessions delivered over 12 weeks with a behavioral health consultant, either in-person or virtually. Feasibility was assessed as recruitment percent and pace and retention percent. Acceptability was assessed with the Client Satisfaction Questionnaire-8 (CSQ-8). Participants completed self-report measures of well-being, depression, substance use, and psychological processes of change at baseline, mid-intervention (6-weeks), and post-intervention (12-weeks). Participants engaged in a brief interview about their experiences at the end of the intervention. Results Twenty-one participants enrolled in the intervention (66.7% female, M age = 44.0 years, 19% of those invited). Participants completed an average of 5.1 BA sessions (SD = 1.6) and most (90%) were retained through 12 weeks. Participants rated the intervention as highly acceptable on the CSQ-8 (M = 30.4/32.0, SD = 1.6). In qualitative interviews, participants reported that working with the therapist and setting values-based goals were helpful, while also recommending more tailoring to patients’ needs and offering the program early in MOUD treatment. Preliminary efficacy data suggest the program was associated with small to moderate improvements in life satisfaction (Cohen’s d = 0.25) and positive affect (d = 0.62), whereas there were no changes in depression (d = 0.09) or negative affect (d = −0.07) in a group with low depression at baseline. Discussion VBA adapted for patients on MOUD in primary care was feasible to deliver and acceptable to participants. Minor modifications to the target population and treatment manual could increase the program’s impact. Future studies will test the efficacy of the intervention in improving quality of life and OUD treatment outcomes. Clinical trial registration https://clinicaltrials.gov/study/NCT05262725, Unique ID: NCT05262725.